Functional proteomics of neuropeptidome dynamics during the feeding process of Rhodnius prolixus - Sterkel, Marcos (2011)
In hematophagous insects, blood intake triggers a prompt response mediated by neuropeptides, which regulates a variety of physiological processes. Here we report a quantitative proteomic analysis of the postfeeding response in the central nervous system of Rhodnius prolixus, a vector of Chagas disease. The concentration of neuropeptides NVP-like, ITG-like, kinin-precursor peptide, and neuropeptide-like precursor 1 (NPLP1) significantly changes in response to blood intake. We also performed a neuropeptidomic analysis of other feeding-related organs, namely salivary glands and gut. We identified NPLP1 in salivary glands and myosuppressin in midgut. This is the first report suggesting a role for NPLP1, involving the peptides processed from this precursor in the hormonal control of the production and/or release of saliva. Our results contribute to the understanding of the postprandial neuroendocrine response in hematophagous and provide important information for physiological and pharmacological studies aimed to the design of next-generation insecticides such as peptidomimetics.